The exposure of French and South Korean firm stock returns to exchange rates and the COVID-19 pandemic - Willem Thorbecke (Journal of Risk and Financial Management, 2021)
Rogoff predicted that the U.S. dollar will depreciate and that exchange rate volatility will return. The coronavirus crisis has also roiled the world economy. This paper investigates the exposure of French and Korean firm stock returns to exchange rate appreciations and the pandemic. Both France and Korea are major exporters, but Korea has managed the crisis better than France. The results indicate that Korean firms have come through the pandemic better than French firms. The findings also indicate that the Korean economy is less exposed to appreciations than the French economy. This paper concludes with suggestions to increase firms' resilience to these shocks.
Keywords: G10; I10; 330; coronavirus; stock returns; exchange rate exposure; France; Korea